2015
DOI: 10.1016/j.annemergmed.2015.07.290
|View full text |Cite
|
Sign up to set email alerts
|

256 A Descriptive Analysis of Patients Who Opt Out of Routine HIV Screening in the Emergency Department

Abstract: The BPA Sepsis Risk Scoring System was created based on the SSC guidelines and guided by the Detecting and Treating Sepsis manual from Epic Systems. A score >2.5 meant that a patient met SIRS criteria, is potentially septic, and triggered the BPA. The definitive diagnosis of sepsis for ED SIRS visits was based upon final diagnostic related group (DRG) coding and further established by imaging modalities, urinalysis, and physical exam findings on chart review. BPAs' sensitivity, specificity, PPV, NPV was calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Research evaluating opt‐out HIV testing has found that it has a positive impact on health outcomes and is generally acceptable to both patients and health care providers across a variety of health care settings . However, researchers have also reported barriers to full implementation, such as ethical concerns among staff performing HIV testing , patients perceiving themselves to not be at risk , and provider discomfort with testing and giving results . A theory‐based strategy could be useful in addressing these barriers.…”
Section: Introductionmentioning
confidence: 99%
“…Research evaluating opt‐out HIV testing has found that it has a positive impact on health outcomes and is generally acceptable to both patients and health care providers across a variety of health care settings . However, researchers have also reported barriers to full implementation, such as ethical concerns among staff performing HIV testing , patients perceiving themselves to not be at risk , and provider discomfort with testing and giving results . A theory‐based strategy could be useful in addressing these barriers.…”
Section: Introductionmentioning
confidence: 99%